2014
DOI: 10.1111/bjd.12925
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological profiles in 17 Japanese patients with drug‐induced pemphigus studied at Kurume University

Abstract: The present study indicated that the majority of the patients with DIP studied showed a pemphigus foliaceus-type phenotype with anti-Dsg1 autoantibodies, caused by thiol-containing drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Other diseases have also been described as occurring concomitant with PH, such as rheumatoid arthritis, psoriasis, thyroid disease, systemic lupus erythematosus, HIV infection, sarcoidosis, myasthenia gravis, and autoimmune hemolytic anemia; however, a direct relationship between these conditions and PH has not been proven.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other diseases have also been described as occurring concomitant with PH, such as rheumatoid arthritis, psoriasis, thyroid disease, systemic lupus erythematosus, HIV infection, sarcoidosis, myasthenia gravis, and autoimmune hemolytic anemia; however, a direct relationship between these conditions and PH has not been proven.…”
Section: Resultsmentioning
confidence: 99%
“…Drug‐induced PH is rare and was reported for only seven patients. Of these instances, three occurred after patients received D‐penicillamine; two, bucillamine; one, thiopronine; and one, an erdosteine‐containing mucolytic agent (patient was a child) …”
Section: Resultsmentioning
confidence: 99%
“…All sera were kept at −80 °C for long durations and at 4 °C with 0·1% sodium azide as a preservative during experiments. Studies of the considerably large number of patients used in this study have previously been reported . All previously reported studies for smaller numbers of patients used in this study are listed in Appendix S2 (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous reported cases of DIP, particularly pemphigus foliaceus (PF) . Medications that cause DIP are categorized into two groups: thiol (SH) drugs, such as penicillamine and captopril, and non‐SH drugs . Candesartan is mainly used in the treatment of hypertension and does not contain SH groups.…”
Section: Cases Of Non‐sh‐drug Induced Pemphigusmentioning
confidence: 99%
“…However, the mechanism for non‐SH drug‐induced DIP is not clear. As far as we searched, 50 cases have been reported of non‐SH DIP including our case (Table ). Of these, 32 cases were positive for active amide (AA) groups or combination of drug with AA groups and other drug.…”
Section: Cases Of Non‐sh‐drug Induced Pemphigusmentioning
confidence: 99%